Soluble CD146 reflects altered endothelial and metabolic homeostasis in peripheral artery disease - Haizam Oubari; Julien Labreuche; Charlotte Reytier; Françoise Dignat-George; Jean-Paul Duong-Van-Huyen; Joseph Emmerich; Pascale Gaussem; Patrick Bruneval; Marcel Blot-Chabaud; Alexandre G. Lellouch; Nathalie Bardin; David M. Smadja (Angiogenesis, 2026)
Background Peripheral Arterial Disease (PAD) is a prevalent but underdiagnosed pathology. Soluble CD146 (sCD146) was described as a marker of endothelial dysfunction and vascular congestion. Objective We hypothesize that sCD146 may represent a novel biomarker of PAD. Our objective was to evaluate the association between plasma sCD146 levels and the occurrence and severity of PAD. Methods In this case–control study, 184 Caucasian men with symptomatic PAD were compared to 163 age-matched healthy control patients. PAD diagnosis was confirmed using ankle-brachial index (ABI) and imaging. Plasma sCD146 was quantified using ELISA. Associations with clinical and biochemical parameters were analyzed through multivariable logistic regression models. Results sCD146 level was significantly reduced in PAD patients (mean [95% CI]: 288 ng/mL [269–306]) versus control patients (480 ng/mL [460–500], p p p = 0.005), but negatively correlated in PAD patients (β = − 0.156, p = 0.041), with significant interaction ( p = 0.002). Age-adjusted OR for PAD was highest in individuals with high HDL-C tertiles (OR = 1.41, 95% CI 1.22–1.63). Conclusion A lower sCD146 concentration is independently associated with PAD. Additionally, an inverse relationship was observed between HDL-C and these patients. These findings suggest that sCD146 may reflect impaired endothelial homeostasis and metabolic dysregulation in PAD, indicating that it could serve as a diagnostic biomarker for the pathology. Clinical trials registration : NCT00377897.